Doxycycline Attenuates Doxorubicin-Induced Cardiotoxicity by Improving Myocardial Energy Metabolism in Rats - Dantas, Danielle [UNESP]; Pereira, Amanda Gomes [UNESP]; Fujimori, Anderson Seiji Soares [UNESP]; Ribeiro, Ana Paula Dantas [UNESP]; de Almeida Silva, Carol Cristina Vágula [UNESP]; Monte, Marina Gaiato [UNESP]; Corrêa, Camila Renata [UNESP]; Fernandes, Ana Angélica [UNESP]; Bazan, Silmeia Garcia Zanati [UNESP]; Azevedo, Paula Schmidt [UNESP]; Minicucci, Marcos Ferreira [UNESP]; de Paiva, Sergio Alberto Rupp [UNESP]; et al. (MDPI, 2022)
Aim: Evaluate the influence of doxycycline, an anti-inflammatory and matrix metalloproteinase (MMP) inhibitor, on the attenuation of chronic doxorubicin-induced cardiotoxicity in rats. Methods: We allocated male Wistar rats into four groups: control (C), doxorubicin (D), doxycycline (inhibitor of MMP, IM), and Dox + doxycycline (DIM). Groups IM and DIM received doxycycline (5 mg/kg, IP) once a week for 4 weeks. In addition, 48 h after every doxycycline injection, groups D and DIM received Dox (5 mg/kg, IP). We performed echocardiogram and evaluated TIMP-4 and collagen I protein expression, MMP-2 activity, and oxidative stress and myocardial metabolism. Results: Doxorubicin promotes left atrium (LA) and left ventricle (LV) dilatation and decreases in LV fractional shortening, which was improved by doxycycline. Moreover, doxycycline attenuated the LV cardiomyocyte hypertrophy and collagen type I expression. Doxorubicin increased phosphofructokinase and decreased beta-hydroxyacyl Co-A dehydrogenase, pyruvate dehydrogenase, citrate synthase, and ATP synthase activity, which was partially attenuated by doxycycline. Lastly, doxycycline improved antioxidant enzyme activity in the DIM group. Conclusion: Doxorubicin increases oxidative stress and promotes changes in myocardial energy metabolism, accompanied by structural and functional changes. Doxycycline attenuated the doxorubicin-induced cardiotoxicity, at least in part, through changes in myocardial energy metabolism.
Keywords: collagen I; doxycycline; MMP-2; myocardial energy metabolism; oxidative stress; TIMP-4